Social school climate and bullying in adolescents. The mediate role of the compassion. - Arreola-Olivarría, Claudia Gabriela; Valdés-Cuervo, Angel Alberto; Morales Álvarez, Agustín; Díaz-Vargas, Luis Alberto; Chaidez-Villalobos, Ileana Danae (Emerging Trends in Education, 2025)
The school context plays an essential role in the prevention of bullying. However, deepening the knowledge of the mechanisms that mediate this influence is necessary. In this context, the study proposed to examine the direct and indirect relationships between school social climate, compassion, and bullying in public high school students in southern Sonora. 450 students (M age = 13.11 years, SD = 0.94) participated in the study, 219 (48.6%) male and 231 (51.4%) female. A mediation model was calculated that showed significant direct negative relationships between the school’s social climate and the frequency of bullying. Additionally, the results confirmed that the school climate decreases the frequency of bullying due to its positive effect on the students’ experience of compassion toward peer victims of aggression. We concluded that a positive school climate is essential to prevent bullying in high school students.